Collaborative Governance dalam Percepatan Penurunan Stunting di Kabupaten Bintan - Qori Hidayasa; Fitri Kurnianingsih; Agus Hendrayady (Bahasa Indonesia, 2023)
The Regional Government of Bintan Regency is trying to reduce the stunting rate. Based on data from the Health Service, the stunting rate in Bintan Regency has decreased, which initially reached 5.23% in 2021, dropping to 3.41% in 2022. There are still problems in accelerating stunting reduction in Bintan Regency, there are several areas with high stunting rates. This study aims to determine the Collaborative Governance process in accelerating stunting reduction in Bintan Regency. Using a qualitative approach to the type of descriptive research. Data collection techniques used are observation, interviews, and documentation. The results of this study (1) Face to face dialogue have been carried out by the stakeholders; (2) Building Trust has been built by itself and through coordination meetings; (3) Process Commitment has been formed and uniform; (4) Shared understanding, vision, mission and goals have been agreed upon, but there are still differences in perceptions regarding the duties and responsibilities; (5) Joint Results, as a whole have been realized, but there are still several areas with high stunting rates.